Skojarzenia słowne osób dwujęzycznych na podstawie języków: polskiego i włoskiego - Lach, Michalina; Nowak, Michał (Investigationes Linguisticae, 2007)
This article is an attempt to explain the basic rules of word associacions of bilingual speakers as well as the matter of the second language acquisition with its cultural implications. The paper deals also with the matter of lexical access with particular stress put on the theory of connectionism. The study is based on the free word association test and was conducted with cooperation with a group of Polish students of the Italian language. The results show a significant correlation between learning a second language and acquiring the culture of its geographic area.